2020
DOI: 10.1515/npprj-2020-0071
|View full text |Cite
|
Sign up to set email alerts
|

Full-field hygro-expansion characterization of single softwood and hardwood pulp fibers

Abstract: The dimensional stability of paper products is a well-known problem, affecting multiple engineering applications. The macroscopic response of paper to moisture variations is governed by complex mechanisms originating in the material at all length-scales down to the fiber-level. Therefore, a recently-developed method, based on Global Digital Height Correlation of surface topographies is here exploited to measure the full-field hygro-expansion of single fibers, i. e. a surface strain tensor map over the full fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 23 publications
4
41
0
Order By: Relevance
“…In contrast, for FD handsheets, the cellulose molecules in the "dislocated regions" contract during drying, retaining its (more or less) amorphous configuration, resulting in a larger hygro-expansion of FD fibers. The lower hygro-expansivity of RD compared to FD fibers (between 30 and 90% RH) was confirmed in (Vonk et al, 2023c) and (Vonk et al, 2023a), and it was indirectly shown (for hardwood fibers) that indeed the hygro-expansion along the micro-fibrils was lower for RD fibers. Furthermore, the alignment of the "dislocated cellulose regions" due to an external force was confirmed using molecular dynamics simulations in (Khodayari et al, 2020).…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…In contrast, for FD handsheets, the cellulose molecules in the "dislocated regions" contract during drying, retaining its (more or less) amorphous configuration, resulting in a larger hygro-expansion of FD fibers. The lower hygro-expansivity of RD compared to FD fibers (between 30 and 90% RH) was confirmed in (Vonk et al, 2023c) and (Vonk et al, 2023a), and it was indirectly shown (for hardwood fibers) that indeed the hygro-expansion along the micro-fibrils was lower for RD fibers. Furthermore, the alignment of the "dislocated cellulose regions" due to an external force was confirmed using molecular dynamics simulations in (Khodayari et al, 2020).…”
Section: Introductionmentioning
confidence: 67%
“…Paajanen et al (2022) showed that during single fiber hygro-expansion up to a RH of 90%, the hemi-cellulose inside the fibers softens between 40 and 60% RH, whereas the cellulose micro-fibrils swell between 55 to 95%. In (Vonk et al, 2021(Vonk et al, , 2023c the transient dimensional changes accompanying these phenomena during hygro-expansion (between 30 and 95% RH) was characterized, revealing curves which are similar to conventional sorption isotherms (Fellers, 2007;Paajanen et al, 2022). However, characterization of paper above M C levels associated with 95% RH remains undiscovered, which according to Salmén et al (1987) is the relevant M C range during which phenomena occur that strongly affect the hygro-expansivity of the paper sheet.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Despite the 10% filtering threshold, it was a posteriori noticed that various pixels surrounding the eliminated data were still too noisy, causing convergence problems in the GDHC procedure. In order to overcome this problem, the regions with missing data values were uniformly expanded in the height profiles by eliminating the one layer of pixels located directly along their circumference, which further reduced the influence of local noisy data on the correlation analysis (Vonk et al 2020(Vonk et al , 2021. Subsequently, the average stress in an ROI was calculated from the applied force and the average cross-section of the ROI.…”
Section: Global Digital Height Correlation Analysismentioning
confidence: 99%